Organizational Communication at the Era of Virtual Reality and Society 5.0 - Hafidh Turmuji; Fauzi Ensa Hidayat; Amirah Rahmawati; Rizky Jumansyah; Leonardi Paris Hasugian (Universitas Komputer Indonesia, 2021)
This research aims to identify how the implementation of organizational communication at the era of Society 5.0 through the technology of Virtual Reality as the most relevant instrument especially in the current COVID-19 pandemic. This research conducted with qualitative methods with literature study. The result of this research take form as the conclusion of what and how the implementation of organizational communication which happens in the era of Society 5.0 via Virtual Reality which certainly be different than conventional interpersonal communication. The research concludes that Society 5.0 is the next milestone in the ever-evolving life phase which situate humanity as the center of the process. Through Society 5.0 and Virtual Reality making it possible as a new plane of interaction with tools like Customizable 3D Avatar, Gesture, and 3D Room Chat. Contradictory to the usual online video calling where we only able to see the video frame of the other party.